ВРЕДИТЕЛИ ЛЕСНЫХ НАСАЖДЕНИЙ В АРИДНЫХ УСЛОВИЯХ КАРАКАЛПАКСТАНА - Мырзамбетов, П.Ш.; Бекназаров, А.; Калжанов, П. (SCIENCE and SOCIETY, 2022)
Adverse environmental factors, such as high temperatures in July and August, the shortage of water resources has led to an excessive drying of the soil and as a consequence - the weakening the tree stand and the death of young plantations. It is known that the weakening of the trees is a signal to pests and diseases, which are massively multiply under conditions favorable to them, may lead to death of plants. The article provides a description of some pests of forest plantations and regulatory issues of their numbers.
Keywords: ecological factor; forest; pests; Amu Darya; trees; caterpillars